(untitled) (Annals of Medical Research, 2021)
Aim: We compared outcomes between “single pathologic N1” (pN1a) and “multiple pathologic N1” (pN1b) patients and investigated whether all pN1b patient subgroups had the same outcomes in non-small cell lung cancer (NSCLC). Materials and Methods: We retrospectively analyzed 487 pN1 patients with NSCLC between 2010 and 2016. There were 284 single N1 (pN1a Group) and 203 multiple N1 (pN1b Group) patients. pN1b Group was divided into two subgroups; invasion of intraparenchymal lymph nodes (pN1b-without hilar group, n=48) and pN1b provided that one of the metastatic lymph nodes LN(s) has to be 10 and/or 11 (pN1b with hilar group, n=155). Overall survival (OS) and disease-free survival (DFS) rates were compared between subgroups of N1 patients. Results: The mean age was 59.3 ± 8.3. The majority of the patients were male (n=462, 94.9%). The OS rate of pN1 patients was 53.2%, while the DFS rate was 48.8%. Multivariate analysis showed that adenocarcinoma histology (p=0.030), presence of pleural invasion (p=0.001) and perineural invasion (p=0.034) had worse effect on overall survival in pN1 patients. Both OS and DFS rates were statistically better in the pN1a Group than the pN1b Group (OS; 56.2% vs 48.3% p=0.03; DFS; 51.9% vs 44.4%, p=0.03). Although both OS and DFS rates were better in the pN1b-without hilar group patients than in pN1b-with hilar group, it was not significant (OS; 56.0% versus 44.5% p=0.187; DFS; 53.9% vs 40.6%, p=0.115). Conclusion: The pN1a Group had significantly better survival than the pN1b Group. However, the patients in the latter group without hilar LN(s) invasion exhibited better survival rates than those with hilar LN(s) involvement, although this was not significant. We think that the survival advantage in multiple N1 without hilar lymph node involvement should be evaluated with a larger patient series.